Policy handbook : access to and participation in continuous vocational education and training (CVET) in Europe - (:unkn) unknown (Publications Office of the European Union, 2014)
"Continuous vocational education and training (CVET) for all is essential to respond to increased global competition and changing technological and socioeconomic requirements. What can be done to make use of the full potential that CVET has to offer individuals, enterprises, society and the economy? How can participation in CVET be increased and access to it extended, especially for disadvantaged groups that traditionally participate the least? How can high-quality provision be ensured? This CVET policy handbook addresses policy-makers, enterprises, social partners and other stakeholders. It aims at strengthening CVET by providing policy guidance illustrated with concrete examples of effective practices. It highlights the importance of CVET for smart and inclusive growth and shows the benefits of investing in it. It gives an overview of the current position in Europe and describes success factors and good practices for widening access and participation and for promoting high-quality CVET provision for all." (Editor, BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.2 Europa; Berufliche Weiterbildung; Weiterbildungspolitik; Weiterbildungsbeteiligung; Bildungschancengleichheit; Best practice; Europa